A belief-centered treatment of pragmatic presupposition - Manara, Lucia H. B. [UNESP]; de Roeck, Anne (Springer Nature, 1997)
Traditional, semantic, accounts of presupposition centre on truth conditional treatments relying on entailments. In contrast, our work concentrates on the investigation of presupposition as a pragmatic phenomenon which interacts with agents’ beliefs. Several accounts (e.g., [1],[2],[5],[6],[7],[8],[23]) have taken contextual factors into account. However, they run into problems caused by the consequences of the basic possible world based notions of propositionhood they deploy, which prevent the formulation of partial, revisable information states. Starting from a notion of proposition developed in property theory ([20],[21],[22]), we develop a formal model of contexts as partial beliefs entertained by agents, who do not necessarily hold accurate or compatible views. We show how this model can be exploited in the treatment of the projection problem for conditionals, conjunctions and disjunctions. We show that a treatment along these lines provides an adequate model of complex presuppositional behaviour, including the projection problem. We contrast our results with those obtained in other approaches.